Green Light-Driven Reduction of Methylenemalononitriles with Formate as a Reductant Without a Thiol Hydrogen-Atom-Transfer Catalyst - Yang, Yong-Qing; Liu, Jialu; Lu, Zheng; Xu, Ximing (Synthesis, 2025)
The reduction of methylenemalononitriles to their corresponding methylmalononitriles represents an important transformation in organic synthesis, owing to the ready availability of these starting materials. Herein, we report a safe, cost-effective, and practical photochemical reduction employing readily accessible organophotocatalyst and formate without thiol-mediated HAT catalysts. This method accommodates a broad substrate scope, including diverse (hetero)aryl-substituted methylenemalononitriles, delivering moderate to excellent yields.
Keywords: Photoreduction; Methylenemalononitrile; Formate; Green light; Rose Bengal; No thiol